# Find the sum of odd natural numbers?

2
by safura

2015-03-05T21:54:57+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
So odd natural numbers are 1 , 3 ,5 ,7 ,9 ............. n terms

so using formula of sum in AP we get

S = 1 + 3 + 5 + ..... n terms

so using S =

so where a = first term

n = no of terms

d = common difference

here the common difference is 3 -1 = 2 = d

first term is 1

so s = n/2{2 + (n-1)2}

⇒ s = n(1 + n - 1 )     cancelling 2

Comment has been deleted
excellent
Comment has been deleted
• Brainly User
2015-03-05T21:55:45+05:30
The sum of the first n odd natural numbers 1+3+5+...+(2(n+1)-1) = (n+1)2  1+3+5+...+(2(n+1) -1) = n2 + 2n+2 -1 but n2+2n+1 = (n+1)2 so we finally have: 1+3+5+...+(2n-1) + (2(n+1) -1) = n2 + (2(n+1) -1) so: 1+3+5+...+(2n-1) = n2 and get: and want to prove that: 1+3+5+...+(2(n+1)-1) = (n+1)2 We add (2(n+1) -1) to this:
Is there an easy way to calculate the some of the first n natural numbers? 1+3+5+...+(2n-1) = ? Let's look at the problem for n = 1,2,3,4,5 1=1=12
1+3=4=22
1+3+5=9=32
1+3+5+7=16=42
1+3+5+7+9=25=52
So the answer seems to be:
1+3+5+...+(2n-1) = n2
Proof 1: We can arrange squares in this way. The big square has n2 little squares. We see that the number of little squares is also 1+3+5+...+(2n-1). Proof 2: We will use induction. Step 1.
For n = 1 it's true that 1 = 2*1-1
Step 2.
We suppose that 1+3+5+...+(2n-1) = n2